Robotics: Science and Systems XI 2015
DOI: 10.15607/rss.2015.xi.030
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of legged locomotion in heterogeneous terrain: universality in scattering and sensitivity to initial conditions

Abstract: Abstract-Natural substrates are often composed of particulates of varying size, from fine sand to pebbles and boulders. Robot locomotion on such heterogeneous substrates is complicated in part due to large force and kinematic fluctuations introduced by heterogeneities. To systematically explore how heterogeneity affects locomotion, we study the movement of a hexapedal robot (15 cm, 150 g) in a trackway filled with ∼ 1 mm "sand", with a larger convex "boulder" of various shape and roughness embedded within. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The following study exemplifies automation's utility in the study locomotion of heterogeneous substrates. 1 S1 S1 S1 S1 S1 S S1 S1 Qian et al [225] have taken the first steps in this ambitious direction with the development of a fully-automated terrain creation system called Systematic Creation of Arbitrary Terrain and Testing of Exploratory Robots (SCATTER, Fig. 2c).…”
Section: Heterogeneous Terrestrial Substratesmentioning
confidence: 99%
“…The following study exemplifies automation's utility in the study locomotion of heterogeneous substrates. 1 S1 S1 S1 S1 S1 S S1 S1 Qian et al [225] have taken the first steps in this ambitious direction with the development of a fully-automated terrain creation system called Systematic Creation of Arbitrary Terrain and Testing of Exploratory Robots (SCATTER, Fig. 2c).…”
Section: Heterogeneous Terrestrial Substratesmentioning
confidence: 99%
“…Using SCATTER, we investigated the locomotor dynamics during interaction with a single 3D printed convex objects of different geometries, textures, burial depths and mobilities. 1 Our study revealed that the complex interaction between a robot with a single boulder could be modelled as a scattering process -depending on the contact position on the boulder, the robot left the heterogeneity with a certain angle of trajectory deviation.…”
Section: Introductionmentioning
confidence: 83%
“…1 For example, we compare robot trajectories during interaction with a single spherical boulder fixed at different burial depths in the sand (Fig. 3A).…”
Section: Scattering Angle Dependence On Leg-boulder Contact Positionmentioning
confidence: 99%
“…In contrast, robots typically avoid most collisions and contacts with their physical environments and treat large disturbances as "obstacles" because our limited understanding of contact reaction forces precludes their effective use. Without a better understanding of the dynamics of repeated locomotorobstacle interactions [3], [5], [6] obtaining such understanding from systematic experiments in simplified settings [7], [8], [9], [10], [11], [12], [5], [13]. While the vast parameter space presented by any natural environment presents daunting challenges to analysis, this paper seeks to build on recent progress in extracting a highly abstracted but physically revealing model of periodic legged gaits interacting with periodically structured obstacle fields [13].…”
Section: Introductionmentioning
confidence: 99%